2012
DOI: 10.1016/j.habitatint.2011.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Conflict or consensus: An investigation of stakeholder concerns during the participation process of major infrastructure and construction projects in Hong Kong

Abstract: a b s t r a c tPublic participation in the planning and design of major public infrastructure and construction (PIC) projects is crucial to their success, as the interests of different stakeholders can be systematically captured and built into the finalised scheme. However, public participation may not always yield a mutually acceptable solution, especially when the interests of stakeholders are diverse and conflicting. Confrontations and disputes can arise unless the concerns or needs of the community are car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 26 publications
2
91
1
4
Order By: Relevance
“…Stakeholders' power over social responsibility issues in construction projects, Journal promote SR is still inadequate. Li et al (2012) found that the public in eastern culture countries is less likely to engage in project decision-making owning to the traditional culture of compliance. It calls for a development of communication channels or stakeholder platforms for project users to put forwards their demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stakeholders' power over social responsibility issues in construction projects, Journal promote SR is still inadequate. Li et al (2012) found that the public in eastern culture countries is less likely to engage in project decision-making owning to the traditional culture of compliance. It calls for a development of communication channels or stakeholder platforms for project users to put forwards their demands.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly agreed that stakeholders have conflicting interests on project objectives (Atkin and Skitmore, 2008). The empirical findings by Li et al (2012) show that the general public care most about land use and environmental issues and that governments focus mainly on economic growth, while NGOs value the green and sustainable techniques most. Having an interest does not necessarily mean having the ability to accomplish the goals.…”
Section: Stakeholder Multiplicity and Dynamicsmentioning
confidence: 99%
“…As one of the most commonly accepted definitions, stakeholders refer to the individuals or groups that can influence or be affected by the urban renewal process [66][67][68]. Those individuals or groups have their own stake or interest in urban renewal projects.…”
Section: Stakeholders' Expectations In Urban Renewalmentioning
confidence: 99%
“…Weighting scales can be constructed for each stakeholder by using ordinal information from 527 the survey in order to state whether a particular aspect is equally, more or less important than 528 another for a given stakeholder (as in Li et al, 2012). For example, decisive and irreversible 529 votes have more weight than oral statements, even the more so when the latter are not 530 repeated or confirmed by subsequent actions.…”
mentioning
confidence: 99%